1999
DOI: 10.1080/02701367.1999.10608029
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Advantages of an External Focus of Attention in Golf

Abstract: This study examined whether the learning advantages of an external focus of attention relative to an internal focus, as demonstrated by Wulf, Höss, and Prinz (1998), would also be found for a sport skill under field-like conditions. Participants (9 women, 13 men; age range: 21-29 years) without experience in golf were required to practice pitch shots. The practice phase consisted of 80 practice trials. One group was instructed to focus on the arm swing (internal focus), whereas another group was instructed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
203
5
24

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(247 citation statements)
references
References 18 publications
15
203
5
24
Order By: Relevance
“…Consequently, the question of how to best train an individual remains unclear. Motor learning theory indicates that the way in which visual feedback variables are selected and presented are most critical to skill acquisition, performance, and retention (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the question of how to best train an individual remains unclear. Motor learning theory indicates that the way in which visual feedback variables are selected and presented are most critical to skill acquisition, performance, and retention (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…External focused coaching points have been shown to aid the learning process (Wulf, 2007;Wulf, Chiviacowsky, Schiller, & Ávila, 2010;Wulf, Lauterbach, & Toole, 1999;Wulf, Mcconnel, Gärtner, & Schwarz, 2002). In addition to this, the PPR and POST demonstrate the control of rhythm within the shots.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies compared the learning effects of altering the attention of golf practice session (see Table 1). These studies assessed the effect of implicit versus explicit learning (Bright & Freedman, 1998;Hardy, Mullen, & Jones, 1996;Kavussanu, Morris, & Ring, 2009;Masters, 1992;Maxwell, Masters, & Eves, 2000;Poolton, Masters, & Maxwell, 2005) or internal versus external focus of attention (Poolton, Maxwell, Masters, & Raab, 2006;Wulf, Lauterbach, & Toole, 1999) on golf performance.…”
Section: Attention During Practicementioning
confidence: 99%
“…The two studies (Poolton, et al, 2006;Wulf, et al, 1999) that compared the learning effect of an internal versus external focus of attention on golf performance both involved novice golfers, a one day acquisition phase and had 21 the retention and/or transfer tests on either the acquisition day or one day later. Wulf et al (1999) reported that the external focus of attention group was significantly more accurate during the chipping tasks than the internal focus of attention group during retention. Poolton et al (2006) also reported that the external focus of attention group significantly improved their putting accuracy during transfer testing, while the internal focus of attention group experienced a reduction in performance.…”
Section: Internal Versus External Focus Of Attentionmentioning
confidence: 99%
See 1 more Smart Citation